WeDoDe: contribuições de uma plataforma digital para a articulação processual do Design Estratégico - Aimi, Marcelo Pereira (Universidade do Vale do Rio dos Sinos, 2012)
The present research has as purpose the structuring of design methodology called Open Strategic Design (OSD) that was based on the collection of knowledge produced by the estrategic design, and motivated by the need for this methodology to be aligned with the contemporaneous social context, marked by the logic of consumption, hyper connected interaction and the nature of symbolic representations. We understand design as rhetoric that organizes the context elements (consumer culture and technological mediation) and language (project, open innovation and strategic design), and, as such, may make differentiated strategic paths. This led to the construction of a digital platform design open and collective, wedode.com, foundation of the application experience and testing of the proposed OSD. The group that participated in the experiment produced material that allowed criticism of the project methodology and insights to be used to change the platform.
Keywords: Design; Design estratégico; Inovação; Metodologia de projeto; Consumo; Strategic design; Open innovation; Crowdsourcing; Innovation; Methodology; Consumer culture; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial